Derivative Spectrophotometric Determination of Uranium(VI) using 2-Hydroxy-3-methoxybenzaldehydeisonicotinoylhydrazone Reagent - RAMESWARA RAO, M.; HARI, K.; DEVANNA, N.; CHANDRASEKHAR, K.B. (Asian Journal of Chemistry, 2010)
A 1:1 (M:L) yellow coloured water-soluble complex of U(VI) is formed with 2-hydroxy-3-methoxybenzaldehydeisonicotinoylhydrazone (HMBIH) in acidic buffer solution. The reaction between U(VI)-HMBIH is instantaneous at pH 4.0 and the absorbance remains constant for more than 2 h. The molar absorptivity and sandell's sensitivity is 1.05 × 104 L mol-1 cm-1 and 0.0238 μg cm2, respectively at λmax 374 nm. Beer's law obeyed in the concentration range of 1.19-11.9 μg/mL. The stability constant of U(VI)-HMBIH complex is 2.08 × 106. The first and second order derivative spectrophotometric determination of U(VI) was carried out by measuring peak height technique at 436 and 441 nm, respectively. This method has been satisfactorily applied for the determination of U(VI) in rock and synthetic samples. The effect of various diverse ions also studied.